THE ROMAN AND LATE ROMAN CERAMICS FROM THE HEROON OF HARBOR STREET AT KNIDOS - Doksanaltı, Ertekin M. (Rei Cretariae Romanae Fautorum Acta, 2022)
Knidos, located in the southwestern part of Anatolia, was an important pottery production and export center during the Hellenistic and Roman Empire periods. A context has been identified in the ‘Heroon of Harbor Street’, a late Roman workshop dating to the first half of the 7th century CE. The coin finds clearly indicate that this site was used during the 6th century CE. and abandoned with the mid-7th century CE. This evidence also makes it safe to say that the ceramic finds date to the early and the first half of the 7th century CE.